PENGARUH PEMASARAN MEDIA SOSIAL PADA KINERJA PEMASARAN: PROPOSISI NILAI SOSIAL PRODUK SEBAGAI VARIABEL MEDIATOR - Hidayat, Yusmar Ardhi; Purnamasari, Eva; Wahyuni, Sri; Astuti, Rifah Dwi; Supaya, Sandi (E-Jurnal Manajemen; Vol 11 No 11 (2022), 2022)
Social media marketing emerges as an appropriate method to assist MSMEs in marketing their products and interacting with their customers during the pandemic and the new normal. MSMEs can build significant business partnerships by engaging consumers as collaborators in actively reviewing and sharing the social value of the product on social media to improve marketing performance. This study had three goals: (1) analyzing the influence of social media marketing on social product value, (2) examining the effect of social product value on marketing performance, and (3) investigating the relationship between the influence of digital marketing and marketing performance. Purposive sampling has been used to select 112 respondents, including culinary MSMEs, that intensively promote their products on social media. Partial Least Squares SEM was used as a research method. According to this study, successful social media marketing raises the value of social products and marketing performance. Social media marketing develops the value of the social product, then improves marketing performance. This study revealed social product value as a moderating variable to empower the positive relationship between social media marketing and marketing performance. Keywords: social media marketing, social product value, marketing performance, and Culinary MSM